2020
DOI: 10.1186/s12876-020-01294-z
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal perforations secondary to a migrated biliary plastic stent successfully treated by endoscope: case-report and review of the literature

Abstract: Background: Endoscopic retrograde biliary drainage (ERBD) is the most frequently performed procedure for treating benign or malignant biliary obstruction. Although duodenal perforations secondary to the biliary plastic stent are quite rare, they can be life-threatening. The treatment strategies for such perforations are diverse and continue to be debated. Case presentation: We report three cases of duodenal perforation due to the migration of biliary plastic stents that were successfully managed using an endos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 26 publications
(23 reference statements)
2
27
0
2
Order By: Relevance
“…Similarly, the prevalence of other complications was not significantly different from the available data. In a large meta-analysis, Cirocchi et al indicated that the risk of perforation during ERCP occurred in 0.6% of cases [27], and cholecystitis was observed in 0.5-5.4% of cases [29]. Duodenal perforation occurs mostly with straight stents [29] that was also shown in our study.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Similarly, the prevalence of other complications was not significantly different from the available data. In a large meta-analysis, Cirocchi et al indicated that the risk of perforation during ERCP occurred in 0.6% of cases [27], and cholecystitis was observed in 0.5-5.4% of cases [29]. Duodenal perforation occurs mostly with straight stents [29] that was also shown in our study.…”
Section: Discussionsupporting
confidence: 86%
“…In a large meta-analysis, Cirocchi et al indicated that the risk of perforation during ERCP occurred in 0.6% of cases [27], and cholecystitis was observed in 0.5-5.4% of cases [29]. Duodenal perforation occurs mostly with straight stents [29] that was also shown in our study. In summary, in patients with benign biliary strictures stent replacement should be recommended in about 3.5 months intervals to avoid cholangitis caused by stent dysfunction, however, the length and location of the stricture affects stent patency duration.…”
Section: Discussionsupporting
confidence: 86%
“…Biliary stent migration occurs in 5–10% of patients [ 6 ]. Although stent migration is reasonably common, gastrointestinal perforation secondary to stent migration is rare with an incidence of less than 1% [ 7 , 8 ]. The large majority of these perforations occur in the duodenum, with jejunal, ileal and colonic perforations being an even rarer entity.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for colonic perforation in the setting of stent migration include diverticular disease and strictures [ 5 , 6 ]. Suggestion has been made that soft plastic pigtail stents opposed to straight plastic stents should be considered in patients with risk factors for perforation in setting of migration [ 5 , 8–10 ]. Biliary stent removal is usually achievable via endoscopic methods.…”
Section: Discussionmentioning
confidence: 99%
“…A serious potential consequence of stent migration is bowel perforation which can happen at any part of the small or large bowel, but fortunately has an incidence of less than 1%[ 3 , 4 ]. The majority of the case reports with bowel perforation secondary to migrated biliary stent describe duodenal or colonic perforations, with very few cases of small bowel perforations.…”
Section: Introductionmentioning
confidence: 99%